2019
DOI: 10.1111/bjhp.12359
|View full text |Cite
|
Sign up to set email alerts
|

Couple‐focused interventions for men with localized prostate cancer and their spouses: A randomized clinical trial

Abstract: Objectives Few couple‐focused interventions have improved psychological and relationship functioning among men diagnosed with localized prostate cancer and their spouses. This study compared the impact of intimacy‐enhancing therapy (IET), a general health and wellness intervention (GHW), and usual care (UC) on the psychological and relationship functioning of localized prostate cancer patients and their partners. Relationship length, relationship satisfaction, and patient masculinity were evaluated as moderato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 56 publications
3
45
0
4
Order By: Relevance
“…As such, the results of the current study con rm the potential bene ts of capitalizing on the cultural representation of football as a sport that builds on and cultivates masculine ideals [22]. As such, the ndings align with a recent study of the effects of couple-focused interventions for men with localized prostate cancer and their spouses, which suggested that endorsement of traditional masculine norms may be requisite for improving psychological and relationship function [9]. Also inherent was the recognition that men can bene t by being with other men to discuss vulnerabilities and uncertainties, potentially alleviating women's aloneness in their caregiver roles.…”
Section: Discussionsupporting
confidence: 82%
“…As such, the results of the current study con rm the potential bene ts of capitalizing on the cultural representation of football as a sport that builds on and cultivates masculine ideals [22]. As such, the ndings align with a recent study of the effects of couple-focused interventions for men with localized prostate cancer and their spouses, which suggested that endorsement of traditional masculine norms may be requisite for improving psychological and relationship function [9]. Also inherent was the recognition that men can bene t by being with other men to discuss vulnerabilities and uncertainties, potentially alleviating women's aloneness in their caregiver roles.…”
Section: Discussionsupporting
confidence: 82%
“…Atendiendo a la potencia en cuanto al tamaño muestral y teniendo en cuenta que una potencia media sería de 50 parejas por condición, solo 6 estudios estarían en el rango superior, siendo los más potentes: el estudio de Manne et al (2017) (10) con una muestra de 151 parejas por condición; y el estudio de Nicolaisen et al (2018) (9) con 102 parejas en la condición de intervención y 96 parejas en atención habitual. (7) [EE.UU] N= 237 Tipo de cáncer: Cáncer de próstata.…”
Section: Resultados Y Discusiónunclassified
“…Sin embargo, en cuanto al resto de criterios, el estudio de Manne et al (2019) (7) parece reunir aspectos más concretos de cara al reclutamiento de la muestra, como son las puntuaciones de 0 o 1 en ECOG (calidad de vida), puntuaciones altas en IES (distrés) o que el 80% de la muestra informe de disfunción eréctil. En este sentido, recoger una muestra con unas características tan concretas permite conocer más datos sobre la problemática existente en la pareja, así como de la forma de intervención que pueda ser más eficaz ante dicha problemática.…”
Section: Participantesunclassified
See 2 more Smart Citations